Peran Non Governmental Organization (GIZ dan LSM Bina Swadaya) terhadap Klaster Susu Sapi Perah di Kabupaten Boyolali - Rizky Madya Wulan; Muhammad Muktiali (Department of Urban and Regional Planning, Diponegoro University, 2013)
The system change of government in Indonesia to a decentralized government system leads to the potential development of local policies through local economic development (LED). Cluster is one part of the local economic development (LED). Most of the cluster is still in semi-formal form where the approach to the Non Governmental Organization (NGO) still can not be fully implemented. Cluster milk of dairy cows in Boyolali is the largest milk producing areas in Central Java. In the cluster of dairy cows formed a partnership with GIZ and Bina Swadaya which is a NGO. The purpose of this study was undertaken to understand the role of NGOs (GIZ and Bina Swadaya) in the cluster and measure the effectiveness of the role of NGOs is done in a cluster of dairy cows in Boyolali. To achieve the objectives, the research approach used is mix method approach where the process of the study sought to combine quantitative and qualitative approaches. This research focuses on understanding the role of NGOs in the cluster performed, measuring the effectiveness of the role of NGOs in the cluster, as well as the implications of the NGOs role in the cluster performed. The analysis process resulted ino a conclusion and recommendations on the role of Non Governmental Organization (GIZ and Bina Swadaya) Against Milk Dairy Cluster in Boyolali.